Pengembangan Aplikasi Mobile Geotagging Fasilitas Tanggap Darurat Bencana Alam Menggunakan Algoritma Polylines sebagai Pencarian Rute Terdekat - Reynald Hermanto Simanjuntak; Herman Tolle; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Natural disasters are conditions of events or natural activities that can cause some negative effects such as damage, loss, suffering and also pessological problems in humans. These natural disasters can occur due to nature itself or because of humans. Indonesia itself is a disaster-prone area so that natural disasters occur frequently in Indonesia. Because of the frequent natural disasters that occur in Indonesia, a disaster risk management system will be needed to handle assistance for natural disasters. One of the problems in the emergency response phase is the determination and selection of ineffective natural disaster emergency response facilities. Therefore, by utilizing geotagging technology, a mobile application can be designed to add location points to natural disaster emergency response facilities. So that users can find the location of natural disaster emergency response facilities easily and the coordinator of each location field can process data from each facility that will be added. By utilizing the Polylines algorithm, it can be used as a route search to get to the location of the facility. Polylines algorithm will provide route depiction and recommend the closest route from the user's location that has been calculated using Google Direction API to the location of the facility furthermore provide alternative routes that can be used by the user. Based on validation testing on the mobile application "Geotagging Fasilitas Tanggap Darurat Bencana Alam" it was found that the application had fulfilled functional requirements. Then the compatibility testing shows that the application can run without problems on three different devices with a percentage of 100%. In the usability test, a score of 77.5 is obtained so that the application is appropriate to use.